Karakteristik Batu Apung sebagai Kreasi Bentuk Meja Tamu - Qoirul Roziqin; Aries Budi Marwanto (Texture:Art and Culture Journal, 2023)
The creation of the final guest table work with the creation of the characteristics of this pumice stone was motivated to create a new variant for developing this type of guest table. The work created consists of three pieces using tamarind wood, gypsum, and resin. The creation methodology uses the theory SP. Gustami includes the stages: exploration, design, and realization. The aesthetic approach to the work refers to Monroe Beardsley's theory in Problems in the Philosophy of Criticism which explains 3 characteristics, unity, complexity, and intensity. The process of working on the work uses carpentry techniques (bench work), chiseling techniques (carving), drilling techniques using a mini grinder, and dot techniques using nails. The finishing of the table is done by applying a brush technique using chemicals, candy-tone paint, coating, and resin to produce attractive wood effects and colors. The final results of the guest table works are three pieces, one of which uses tamarind wood, and two works use a combination of tamarind wood and gypsum. This creation is oriented towards developing coffee table designs, to create products that have a novelty value and keep abreast of market developments.